An Experimental Investigation on Transpiration Cooling Part II: Comparison of Cooling Methods and Media. (2004) - Wang, J. H.; Messner, J.; Stetter, H.
Abstract : This article attempts to provide a cooling performance comparison of various mass transfer cooling methods and different cooling media through two experiments. In the first experiment, pressurized air was used as a cooling medium and two different circular tubes were used as specimens. One is made of impermeable solid material with four rows of discrete holes to simulate film cooling, and the other consists of sintered porous material to create a porous transpiration cooling effect. The natures of transpiration cooling and film cooling including leading and trailing edge injection cooling were compared. This experiment found that by using a gaseous cooling medium, transpiration cooling could provide a higher cooling effect and a larger coolant coverage than film cooling in the leading stagnation region, and on the side of the specimen at the same coolant injection flow rates; but in the trailing stagnation region, the traditional coolant injection method through discrete film holes might be better than transpiration cooling, especially for turbine blades with thin trailing edges. In the second experiment, the cooling effects of gaseous and liquid media on the same porous tube's surface were compared. This experiment showed that the porous areas cooled using gaseous and liquid cooling media were almost identical, but the cooling effect of liquid evaporation was much higher than that of gaseous cooling, especially in the leading and trailing stagnation regions of turbine blades. This important discovery makes it possible to solve the stagnation region problems in turbine blade cooling.